Wettability study of hydrophilic nickel coatings with high surface energy and high-temperature wear resistance. (March 2023) - Yue, Bowen; Chang, Zheng; Wang, Sen; Gao, Xujie; Guo, Nana; Wang, Yanwei; Zhai, Xiaoqing; Zhu, Guangming
Abstract: The paper aims at enhancing the metal-hydrophilicity and high-temperature wear resistance of copper wheels to prepare amorphous ribbons. Nickel layers with various microstructures were prepared onto the polished copper plates by electrodeposition and subsequent chemical etching. The surface characteristics, phase composition, liquid contact angle and surface free energy of coatings were studied to reveal the specific influencing factors of wettability variation in working and idle states. The study found that some etched surfaces can maintain a high level of surface energy and hydrophilicity after aging and wear. The roughness of the modified surface with large-sized hierarchical crater structure and thistle prismatic structure reached 465 nm and 551 nm, which can remain a high surface energy during the 300 °C of aging. The contact angle of molten aluminum and tin on these two surfaces were 60.4° and 55.7°, 20.2° and 17.1°, much smaller than the surface of polished copper. The prepared surfaces with multi-branch structure and large-sized hierarchical crater structure were able to remain large Lewis acid-base interaction, which were 7.45 mJm −2 and 7.82 mJm −2 . However, the surface with a thistle prismatic structure had obvious abrasive wear characteristics, and the surface energy was only 5.86 mJm −2, even lower than the 6.29 mJm −2 of the worn copper surface. This manuscript provides a reference for improving the long-term metal-hydrophilicity and wear resistance of the solidified substrate. Graphical Abstract: ga1 Highlights: The modified surfaces have long-term high-temperature metal-hydrophilicity and wear resistance. The van Oss-Chaudhury-Good method was applied to evaluate surface free energy by three kinds of probe liquids. This paper provides a new method to improve the quality of ribbons and the lifespan of cooling wheels.